Pengaruh Harga, Lokasi, Membership Card Terhadap Minat Beli Konsumen Di Swalayan Surya Wates Kabupaten Kediri - Handayani, Rika (Jurnal Cendekia Manajemen (JCM); Vol 1 No 2 (2023): JulyDO - 10.32503/jcm.v1i2.4377, 2023)
The large number of business actors in the same field will increase competition. The formulation of the problem in this research is whether there is a partial or simultaneous relationship and influence and the most dominant influence between price, location and membership card on purchasing interest at Surya Wates Supermarket, Kediri Regency. By knowing the relationship and influence and the most dominant influence between price, location and membership card, you can determine the company's next policy.The total population in this study was 3,413 people, while the sample in this study was 98 respondents using random sampling techniques. Primary data collection techniques use observation, interviews and questionnaires while secondary data comes from books and journals.The multiple linear regression test shows that price, location and membership card simultaneously influence purchasing interest with the F test results showing a significance level of 0.000 and an F value of 6.745. The price, location and membership card variables also partially influence purchasing interest with the membership card variable having the most dominant influence on purchasing interest with a regression coefficient value of 0.711.